THE SPATIAL DISTRIBUTION OF INDONESIA’S MANUFACTURING INDUSTRIES: AN EXPLORATORY SPATIAL DATA ANALYSIS - Edy Santoso; Regina N. Wilantari (UNEJ e-Proceeding)
The issues of spatial distribution of manufacturing industries are important to economic policy. In this paper we contribute to the empirical literature on the spatial distribution of manufacturing sector by taking spatial dependence among region units explicitly into account. The main objective of this paper is to analyze the space-time dynamics of spatial distribution of manufacturing industries in Indonesia. For the methodology, Exploratory Spatial Data Analysis (ESDA) Global Moran’s I was used to determine the general level of spatial autocorrelation in the data based on the province level of manufacturing industries establishments data for the year 2006 to 2015. The results show strong evidences of global spatial autocorrelation in the distribution of manufacturing industries in Indonesia. The result shows that the distribution of Indonesia’s manufacturing industries are unevenly distributed. The Moran’s I statistic analysis, indicates a strong positive spatial autocorrelation in research area and discribes the phenomenon pattern expressed is clustered. A high concentration of manufacturing industries is seen in the several provinces only, as well as in Java island. The moran’s I are tend to decrease along the periode of study. From the LISA, we can ascertain that there was statistically significant high clustering. Only some provinces really show significant clustering and these provinces are West Java, Banten, DKI Jakarta, Central Java, and East Java.